Experimental study on seismic behavior of steel plate reinforced concrete composite shear wall. (1st April 2018) - Wang, Wei; Wang, Yan; Lu, Zheng
Highlights: A novel type of composite shear wall is proposed and studied. Influences on seismic performances are experimentally analyzed. Hysteretic curve model and shearing capacity are generalized based on test data. Test shows the proposed composite shear wall has excellent seismic behaviors. Abstract: Steel plate reinforced concrete composite shear wall (abbreviated as SPRW) is a novel type of composite shear wall which consists of a steel plate incased in the middle of a reinforced concrete shear wall. This arrangement aims at improving the performance of the wall, as steel plate can effectively increase the seismic behavior and concrete can protect steel plate from bulking and corrosion. In this paper, a total of 16 SPRW specimens and 3 traditional reinforced concrete (RC) walls are designed for the cyclic loading test to study the seismic performances, including failure phenomena, failure mechanism, load carrying capacity, ductility and energy dissipation characteristics, etc. Based on the extensive experimental results, the influences on the seismic behavior of SPRW are analyzed through varying parameters, e.g. aspect ratio, thickness of the wall and the steel plate, structural detailing. Finally, the hysteretic curve model and shearing capacity are generalized based on massive test data, and the design formula of shearing capacity is also proposed based on current design codes.